Sales and sales management - Blythe, James (Henry Stewart Talks, 2012)
The role of the salesperson, Personal selling and the communications mix, Sales force functions, Characteristics of successful salespeople, Types of salesperson, Definitions of sales terminology, Preparing for the presentation, Objection handling, Closing the sale, Post-presentation activities, Negotiation, Role of the sales manager, Factors in sales force success, Recruitment of salespeople, Training of salespeople, Remuneration of salespeople, Motivating salespeople, Running a sales meeting